Características de carcaça e qualidade da carne de borregos Morada Nova de diferentes classes sexuais submetidos a restrições alimentares - Araújo, Thiago Luís Alves Campos de (2016)
The present study has a goal of evaluating the sexual classes and feeding restriction levels on the quantitative and qualitative characteristics of Morada Nova’s lamb carcasses. Thirty-five animals with initial body weight of 14,5 ± 0,89 kg were used in a completely casualized experimental delineation, in a 3x3 factorial scheme, being three sexual classes (11 whole males, 12 castrated males and 12 females) and three levels of feeding restriction (0% or ad libitum, 30% e 60%). The dry matter intake and the average daily gain were higher in whole males (P<0,05) followed by castrated males and females. The characteristics of the carcasses were influenced (P<0,05) by sexual classes and feeding restriction. Whole males presented greater hot and cold carcass weights, followed by castrated males and females. However, the yield of the hot carcass was higher in females (45,25%) and castrated males (44,06%) compared to whole males (42,09%). Concerning meat quality, the luminosity values were influenced (P<0,05) by the sexual classes, with whole males presenting higher value (39,74) compared to castrated males (38,19 and females (37,47). The profile of fatty acids of the meat was not affected (P>0,05) by the sexual classes. The concentrations of palmitic acids (C16:0), palmitoleic acids (C16:1c9), stearic acids (C18:0) and oleic acids (C18:1c9) were higher (P<0,05) in the meat of the lambs submitted to 0 to 30% of feeding restriction in relation to the meat of those restricted to 60%. The concentration of desirable fatty acids was greater in the meat of animals fed ad libitum (2827,41 mg/g of meat) and submitted to 30% feeding restriction (2770,69 mg/g of meat) compared to those submitted to 60% (1697,89 mg/g of meat). Animals of distinct sexual classes produce carcasses with different quantitative characteristics without having total influence on meat quality. The lipid profile of the meat is less favorable to consumer’s health when the animals are submitted to 60% feeding restriction.